2013
DOI: 10.4236/ape.2013.31007
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Selected Haematological Parameters in a Female Team during the 25th African Handball Winners’ Cup Played at Cotonou (Benin)

Abstract: The performance in team sports partly depends on the oxygen transport capacity that is also associated with the erythrocyte values, which should be regularly assessed throughout the sports season. This controlled observational study aims at measuring the haematologic modifications induced by the physical load associated with a series of matches in a Benin Division 1 female handball team. It was carried out at Cotonou during the 25th African Handball Winners’ Cup, with 22 female h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In most research studies, soccer players are classified into four groups: forwards or attackers, midfielders, defenders, and goalkeepers. Players of different positions have a very different workload during a game: midfielders run the longest distances (up to 11-11.5 km) compared to forwards or defenders whereas goalkeepers run around 4 km (10). Previous studies have reported that each specific playing position may have unique physical and physiological requirements (29).…”
Section: Introductionmentioning
confidence: 99%
“…In most research studies, soccer players are classified into four groups: forwards or attackers, midfielders, defenders, and goalkeepers. Players of different positions have a very different workload during a game: midfielders run the longest distances (up to 11-11.5 km) compared to forwards or defenders whereas goalkeepers run around 4 km (10). Previous studies have reported that each specific playing position may have unique physical and physiological requirements (29).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the repetitive character of this situation, neither the direct actors nor the leaders at different levels do very much to control the factors causing this absence of constant satisfactory results. Most reflections and scientific publications on the question in Beninese athletes were limited to the purely physiological aspects during team sports competitions (Bio Nigan et al, 2013;Messan et al, 2012;Tonon et al, 2012;Gouthon et al, 2011;Gouthon et al, 2009;Tonon et al, 2009). The rare scientific publications relating to the organizational analysis of sport in Benin were interested in the evolution of sports policy (Gouda, 2010;Dakpo, 2007;Chifflet and Gouda, 1992), with that of the performances and the institutions in charge of its management since 1960 (Gouda and Kpazaï, 2012).…”
Section: Introductionmentioning
confidence: 99%